Therapeutic Utilities of Pediatric Cardiac Catheterization - A. Moustafa, Giannis; Kolokythas, Argyrios; Charitakis, Konstantinos; V. Avgerinos, Dimitrios (Current Cardiology Reviews, 2016)
In an era when less invasive techniques are favored, therapeutic cardiac catheterization constantly evolves and widens its spectrum of usage in the pediatric population. The advent of sophisticated devices and well-designed equipment has made the management of many congenital cardiac lesions more efficient and safer, while providing more comfort to the patient. Nowadays, a large variety of heart diseases are managed with transcatheter techniques, such as patent foramen ovale, atrial and ventricular septal defects, valve stenosis, patent ductus arteriosus, aortic coarctation, pulmonary artery and vein stenosis and arteriovenous malformations. Moreover, hybrid procedures and catheter ablation have opened new paths in the treatment of complex cardiac lesions and arrhythmias, respectively. In this article, the main therapeutic utilities of cardiac catheterization in children are discussed.
Keywords: interventions